High glucose modulates IL-6 mediated immune homeostasis through impeding neutrophil extracellular trap formation - Joshi, Manjunath B.; Lad, Apurva; Bharath Prasad, Alevoor S.; Balakrishnan, Aswath; Ramachandra, Lingadakai; Satyamoorthy, Kapaettu (FEBS letters, 2013)
•High glucose impedes and delays NET formation.•Neutrophils from diabetic subjects respond weakly to NETosis.•Hyperglycemia induces a constitutively active pro-inflammatory condition in neutrophils.•IL-6 is a potent inducer of NETs and effects are abrogated by high glucose. Neutrophils serve as an active constituent of innate immunity and are endowed with distinct ability for producing neutrophil extracellular traps (NETs) to eliminate pathogens. Earlier studies have demonstrated a dysfunction of the innate immune system in diabetic subjects leading to increased susceptibility to infections; however, the influence of hyperglycemic conditions on NETs is unknown. In the present study we demonstrate that (a) NETs are influenced by glucose homeostasis, (b) IL-6 is a potent inducer of energy dependent NET formation and (c) hyperglycemia mimics a state of constitutively active pro-inflammatory condition in neutrophils leading to reduced response to external stimuli making diabetic subjects susceptible to infections.